ANALGESIC AND NEUROPHARMACOLOGICAL EFFECT ON ETHYL ACETATE EXTRACT OF IPOMOEA PES-TIGRIDIS IN ALBINO MICE - Md Rabiul Hossain Chowdhury; Rocky Saha; Kazi Md. Minhazul Islam; Kaniz Fatema; Farjana Afrin; Mir Monir Hossain; Ayan Saha (European Scientific Journal, ESJ, 2014)
The present study was performed to investigate the probable analgesic and neuropharmacological activities of the ethyl acetate extract of Ipomoea pes-tigridisLinn. We designed our study to search new analgesic drug from plants which may be harmless to humans as available drugs for the management of pains, fever have many known adverse effects. In phytochemical screening, it was also found the presence of flavonoids, glycosides, alkaloids, saponins, carbohydrates and tannins which have been reported to be responsible for the analgesic activity in many studies. In addition, comprehensive studies have not been performed yet to justify potential CNS responses of the selected plant. In analgesic studies, the extract of Ipomoea pes-tigridis showed significant analgesic activity(p< 0.05-0.000)both acetic acid induced writhing test and hot plate method in mice. In acetic acid induced writhing model, the extract showed 16.5 6% and 33.125% of inhibition of writhing response at 100mg/kg and 200mg/kg respectively. 100mg/kg dose exhibit maximum nociception inhibition at 30 min and 200 mg/kg exhibit highest nociception inhibition also at 30 min. 200 mg/kg extract exhibit basal reaction time 14 and 100 mg/kg extract exhibit basal reaction time 13.8, ,where the positive control shows basal reaction time 12.8 at 30 min. In case of neuropharmacological effect, the extract didn’t display any significant dose dependent depression of motor activity as well as exploratory behavior in both hole cross method and open field test. The results of this present study suggest that the extract possesses analgesic effect but it doesn’t have any CNS depressant activities. The plant extract might contain CNS stimuli effect and further investigation is required for the confirmation.